Mind Mapping as Efficient Tools in Mathematics Education - Kontrova, Lydia (Communications - Scientific letters of the University of Zilina, 2014)
There are many possibilities how to improve mathematical education and enable students to participate in the process of the cognition of new knowledge. In this paper we present mind mapping as one of graphical representation of mathematical networks which may become another efficient tool for improving mathematical achievement. A pedagogical experiment, whose results are stated in this article, was realised during the academic year 2013/2014 when Mathematics 1 was taught on the Faculty of Civil Engineering, University of Zilina. It consisted in the inclusion of mind maps in mathematics teaching, observation of their influence on the teaching process efficiency.